Psycholinguistic Factors Influencing Vocabulary Acquisition in Young Learners - Achmad Ridwan; Yani Lubis (Jurnal Pendidikan dan Sastra Inggris, 2024)
This study explores the psycholinguistic factors that influence vocabulary acquisition in young learners, focusing on the roles of working memory, phonological processing, and attentional control. Using a qualitative descriptive design, data were collected through classroom observations, interviews, and language task analysis involving children aged 6–8. The findings reveal that vocabulary learning is shaped by the interaction of these cognitive mechanisms rather than exposure alone. Children with stronger working memory retained new words more effectively, while those with higher phonological awareness encoded and retrieved sound patterns with greater accuracy. Attentional control further contributed to how deeply learners processed linguistic input, significantly affecting their ability to understand and store new vocabulary. The results demonstrate that vocabulary acquisition is a dynamic cognitive process dependent on individual differences in memory, sound processing, and attention. These insights highlight the need for instructional practices that address learners’ cognitive profiles and support more effective vocabulary development in early education.